Relevansi Judul dengan Teras Berita pada Kanal Peristiwa di Netralnews.com Periode 30 Maret - Maria Septian Riasanti Mola (JURNALISTIK DAN MEDIA, 2025)
This study aims to determine the relevance between news headlines and leads in the Peristiwa section of netralnews.com during the period of March 30, 2025. The research employs a descriptive qualitative method through direct observation of 16 news articles published within that period. The findings show that most of the analyzed articles fulfill the principle of relevance between headline and lead, although several are found to be inconsistent due to deviations from the lead content. Such inconsistencies tend to arise from clickbait practices aimed at increasing reader engagement. This study emphasizes the importance of consistency between headlines and leads as part of journalistic ethics and maintaining the credibility of online media.